HR Strategies in Increasing Employee Engagement in Generation Z: A Literature Review - Abdul Rahman; Ali Supriadi; Marwana (Fakultas Ekonomi Universitas Muhammadiyah Palu, 2025)
This research aims to explore effective human resource management (HR) strategies in increasing employee engagement among Generation Z. By understanding their characteristics and preferences, this research identifies key factors that influence employee engagement and formulates HR strategies that can improve retention, motivation, and engagement among Generation Z. By understanding their characteristics and preferences, this study identifies the key factors that influence employee engagement and formulates HR strategies that can improve the retention, motivation, and productivity of the Generation Z workforce. This study uses a systematic literature review method with a descriptive-qualitative approach. Data was collected from scholarly journals, industry reports, and reputable academic publications focusing on Generation Z employee engagement. Analysis was conducted by synthesizing previous research findings to identify patterns, trends, and strategic recommendations in improving employee engagement. The results show that employee engagement among Generation Z is influenced by four main factors: (1) work flexibility, (2) technology-based communication, (3) employer branding, and (4) career development opportunities. The findings confirm that companies need to implement more adaptive policies, such as a flexible work environment, utilizing technology in communication, strengthening company values through employer branding, and providing clear career paths. This study provides insights for organizations in designing HR policies that are more relevant to the needs of Generation Z. By implementing strategies that focus on flexibility, technology, and career development, companies can increase employee engagement and loyalty, which in turn has a positive impact on organizational productivity and competitiveness.